The endgame of globalization - Smith, Neil 1954-2012 (Routledge, 2005)
'The Endgame of Globalization' argues that US actions since 9/11 represent the final stage in its century-long effort to complete the project of making US-led globalization a concrete reality across the world.
Includes bibliographical references and index
Keywords: Geschichte 1989-2003; Buitenlandse politiek; Eigenbelang; Geopolitiek; Géopolitique - États-Unis; Liberalisme; Libéralisme - États-Unis; Mondialisation - Histoire; Nationalisme; Neoconservatisme; Außenpolitik; Geschichte; Globalisierung; Nationalismus; Geopolitics -- United States; Globalization -- History; Liberalism -- United States; Weltpolitik; États-Unis - Relations extérieures - 1989-; USA; United States -- Foreign relations -- 1989-